Sequelae of COVID-19 at long-term follow-up after hospitalization - N. V. Pogosova (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2022)
Aim. To assess long-term sequelae of COVID-19 in hospitalized patients at 3 to 7 months after discharge.Material and Methods. The whole of 700 patients hospitalized to the temporary COVID-19 treatment center hosted by the FSBI “National Medical Research Center of Cardiology” of the Ministry of Health of Russia from April to June 2020 were invited to participate in a follow-up study. At 3-7 months after the index hospitalization, patients or their proxies were contacted via telephone in order to obtain information on their vital status, cardiovascular and other conditions or their complications, and new hospitalizations. In addition, patients were invited to an outpatient visit under the "COVID-19-follow-up" program, encompassing physical examination and a comprehensive battery of laboratory and instrumental tests, including spirometry, chest computed tomography (CT) and the six minute walk test (6MWT). Further, dyspnea was assessed using the mMRC (Modified Medical Research Council) Dyspnea Scale. Results: We were able to contact 87.4% (612/700) of patients or their proxies. At follow-up, 4.4% (27) patients died, of which 96.3% (26) had cardiovascular diseases (CVD). A total of 213 patients aged 19 to 94 years old (mean age 56.8±12.5, median 57 years [49.0; 64.0]; men, 55.4%) agreed come for an outpatient visit and to participate in the “COVID-19-follow-up” program. Since discharge, 8% (17) of patients required new hospitalizations, and more than a half of these patients (58.8%; 10/17) had CVD-related hospitalizations. A total of 8.4% (18) patients experienced worsening of hypertension, 9 (4.2%) patients had newly diagnosed hypertension, 2 (0.9%) – coronary artery disease patients experienced new/recurrent angina symptoms. 4 (1.9%) patients had newly diagnosed coronary artery disease, and one patient had an ischemic stroke. At the outpatient visit, 114 (53.5%) patients had some symptoms, most frequently, shortness of breath (33%), fatigue (27.4%), chest pain (11.3%), and abnormal heartbeats (8.5%). Based on the mMRC Scale, 59% of patients had dyspnea of varying severity. Most patients had a normal vital capacity (VC), which was moderately reduced in 3.3% and severely reduced in 0.5% of patients. Chest CT scans were obtained in 78 (36.6%) patients, whose worst lung damage scores during hospitalization were CT3 or CT4. One in ten patients (10.8%) with severe lung damage during acute infection had persisting ground glass opacities, 35.9% developed fibrotic changes, 79.6% of patients had linear or fine focal opacities. According to the 6MWT data, 12.3% of patients walked less than 70% of the predicted distance, 67% walked 71 to 99% of the predicted distance, and 20.7% of patients were able to walk 100% of their predicted distance.Conclusion. These data suggest long-term negative sequelae of COVID-19 in more than half of hospitalized patients.